2020
DOI: 10.29322/ijsrp.10.03.2020.p9936
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 500Hz Tonebursts and 500Hz octave Chirps for Cervical Vestibular Evoked Potentials

Abstract: The Cervical-Vestibular evoked Myogenic potential(c-VEMP) is a biphasic surface potential recorded from the belly of Sternocleidomastoid muscle (SCM) followed by presenting a short loud sound. Various studies have been done with different stimulus to obtain better VEMP responses. The present study is aimed at comparing the c-VEMP responses (amplitude and latencies) of 500 Hz tone burst with 500Hz octave chirp (360-720Hz). c-VEMP was administered on 60 ears from 30 subjects. After preparation, responses were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…In several studies, higher amplitude values were obtained with CHIRP stimulus. 13 , 17 , 18 , 19 Besides, lower amplitude values were reported in other studies. 14 , 16 , 20 Moreover, a study indicated that there was no significant difference between tone burst and CHIRP stimulus results.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…In several studies, higher amplitude values were obtained with CHIRP stimulus. 13 , 17 , 18 , 19 Besides, lower amplitude values were reported in other studies. 14 , 16 , 20 Moreover, a study indicated that there was no significant difference between tone burst and CHIRP stimulus results.…”
Section: Resultsmentioning
confidence: 51%
“…Shorter P1 and N1 latencies have been reported with the CHIRP stimulus in the cVEMP test. 13 - 16 , 17 However, a study stated that longer P1 and N1 latencies were obtained with CHIRP stimulus. 18 Findings of cVEMP amplitude with CHIRP stimulus are contradictory in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…22 Wang et al, Moinudeen et al, and Walther and Cebulla state that CHIRP stimuli produce higher amplitude values in the cVEMP test. 15,22,23 19,20 Ocal et al, and Aydın and Erbek stated that there was no statistically significant difference between CHIRP and tone burst stimuli findings. 18,21 There is only one study in the literature reporting cVEMP threshold values.…”
Section: Cvemps Results With Chirp Stimuli In Healthy Individualsmentioning
confidence: 95%
“…VEMP amplitude differences between the chirp and TB have previously been attributed to the difference in frequency composition of each stimulus (Wang et al 2014). The chirp is comprised of a specific band of frequencies, whereas the TB is a short, single-frequency stimulus (Moinudeen et al 2020). Thus, the frequency-specific chirp stimulus increases the number of irregular afferent neurons that are stimulated, providing larger amplitudes than the TB stimulus (Bas et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Karacayli et al (2020) also found larger N1-P1 amplitudes and shorter latencies for oVEMPs evoked by a 500 Hz NB CE-Chirp as compared with that evoked with a 500 Hz TB stimulus. Significantly larger cVEMP P1-N1 amplitudes for 500 Hz NB chirp compared with 500 Hz TB have been reported (Moinudeen et al 2020). Shorter latencies and smaller amplitudes for cVEMPs evoked by BB chirp stimulus containing several frequencies (500 to 4000 Hz) compared with a 500 Hz TB stimulus have been described (Ozgur et al 2015).…”
Section: Introductionmentioning
confidence: 98%